2001
DOI: 10.1111/j.1151-2916.2001.tb01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Preparation of BaTiO3‐Based Dielectrics, Using Ultrafine Raw Materials

Abstract: BaTiO 3 and Ba(Ti,Zr)O 3 dielectric powders have been prepared from submicrometer BaCO 3 , TiO 2 , and ZrO 2 . By use of submicrometer BaCO 3 the intermediate formation of Ba 2 TiO 4 second phase can be widely suppressed. Monophase perovskites of BaTiO 3 were already formed at 900°C and Ba-(Ti,Zr)O 3 at 1050°C. Aggregates of very small subgrains could be easily disintegrated to particle sizes <0.5 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 11 publications
(16 reference statements)
0
63
1
3
Order By: Relevance
“…Moreover, such wet chemical routes cost too much and are not suitable for mass production. Recently, the advent of purer and finer starting materials at a reasonable price promote the solid-state route to synthesize fine BaTiO 3 powder in lower temperature by using fine or nanocrystalline raw materials [3,[12][13][14]. However, it could lower the crystallinity with decreasing the firing temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, such wet chemical routes cost too much and are not suitable for mass production. Recently, the advent of purer and finer starting materials at a reasonable price promote the solid-state route to synthesize fine BaTiO 3 powder in lower temperature by using fine or nanocrystalline raw materials [3,[12][13][14]. However, it could lower the crystallinity with decreasing the firing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, it could lower the crystallinity with decreasing the firing temperature. On the other hand, it is well believed that for the conventional solid state reaction the morphology and size of BaTiO 3 is primarily determined by the size of the raw materials [11][12][13] and the homogeneity of the mixture [14]. The common solution to the homogeneity problem is just to increase the mixing time but take little effect [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…When its grain size in bulk body is 0.6-0.8 m, the properties are generally optimal [3]. Accordingly, one should use BaTiO 3 particles of 100-200 nm as the starting material taking into account the grain growth that occurs during the sintering process [4][5][6]. Conventional solid-state reaction is one of the most commonly used synthetic methods for fabricating pure BaTiO 3 particles; however, it often requires a high calcination temperature to obtain pure BaTiO 3 phase and the final product is usually coarse and seriously agglomerated which fails to satisfy industrial needs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have clearly shown that the reduction of the particle size of the raw materials (BaCO 3 and TiO 2 ) to submicrometer or even to nanoscale results in a significant decrease of the calcination temperatures. [1][2][3] By using the submicrometer BaCO 3 (d 50 = 0.17 μm) and fine TiO 2 (d 50 = 0.2 μm), single phase of BaTiO 3 was almost obtained at 900 °C for 6 h. 1 The formation of BaTiO 3 by solid-state reactions of nanocrystalline BaCO 3 and TiO 2 powders was completed at 700-800 °C. [2][3] In addition, mechanochemical effects are known to be quite effective to reduce the calcination temperatures for solid-state reactions.…”
Section: Introductionmentioning
confidence: 99%